2022
DOI: 10.1007/s00784-021-04363-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of SARS-CoV-2 IgG antibodies among dental teams in Germany

Abstract: Objectives During the corona pandemic, dental practices temporarily closed their doors to patients except for emergency treatments. Due to the daily occupational exposure, the risk of SARS-CoV-2 transmission among dentists and their team is presumed to be higher than that in the general population. This study examined this issue among dental teams across Germany. Materials and methods In total, 2784 participants provided usable questionnaires and dry blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…In dental settings, aerosol transmission can also occur in specific situations where procedures that generate aerosols are realized. In our systematic review, the number of protective measures, use of rubber dam, type of aspirating system and the presence of HEPA filters utilization seem to affect the prevalence of SARS‐CoV‐2 infection across dental clinics with very low certainty of evidence 30,39 . A recent systematic review found that SARS‐CoV‐2 RNA can be detected in the air in various health care settings and can also be detected in community settings, sometimes at low concentrations.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In dental settings, aerosol transmission can also occur in specific situations where procedures that generate aerosols are realized. In our systematic review, the number of protective measures, use of rubber dam, type of aspirating system and the presence of HEPA filters utilization seem to affect the prevalence of SARS‐CoV‐2 infection across dental clinics with very low certainty of evidence 30,39 . A recent systematic review found that SARS‐CoV‐2 RNA can be detected in the air in various health care settings and can also be detected in community settings, sometimes at low concentrations.…”
Section: Discussionmentioning
confidence: 87%
“…However, only seven 34,36,37,39,40,42,46 and eight 30,34,36,37,39,40,42,46 studies provided detailed information on testing sensibility/specificity and testing trademark, respectively. Only two studies disclosed conflict of interest, 32,36 and eight studies presented funding by diverse companies 30,36,37,39–41,46 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, research into risks of COVID-19 by occupation would be based on cases ascertained through systematic prospective follow-up of large cohorts of workers, with regular ascertainment of symptoms, clinical signs, and polymerase chain reaction (PCR) testing. As that has not been feasible, researchers have been forced to use proxy measures of incidence based on: PCR testing (4)(5)(6)(7)(8)(9)(10)(11), measurements of specific immunoglobulins against SARS-CoV-2 (12)(13)(14), symptoms and sickness absence (6), COVID-19 related hospital admission (7,15,16), or mortality from the disease (7,15,(17)(18)(19)(20)(21)(22). In most studies to date, with broad coverage of occupations, mortality from COVID-19 has been the outcome measure (7,15,(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Therefore, right after onset of the COVID-19 pandemic, it was discussed that health care professionals (HCPs) from disciplines with close patient contact, where no face masks can be worn by the patients during examination and therapy, could be at high risk for nosocomial infection with SARS-CoV-2, including dentists, maxillofacial surgeons, and otorhinolaryngologists ( Meng et al 2020 ; Peng et al 2020 ). Although recent data suggest that dental practice personnel are at no higher risk for infection with SARS-CoV-2 as compared to the general public ( Araujo et al 2021 ; Mksoud et al 2022 ), there are also reports stating high infection risks for dentists as well as for HCPs from other specialties ( Nguyen et al 2020 ; Sarapultseva et al 2021 ). Among other measures such as personal protective equipment, preprocedural mouthwashes have been discussed and recommended from the early stages of the pandemic for temporarily reducing the intraoral viral load and infectivity in SARS-CoV-2–positive individuals ( Gottsauner et al 2020 ; Herrera et al 2020 ; Meister et al 2020 ; Meng et al 2020 ; Peng et al 2020 ; Meister et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%